Necroptosis contributes to chronic inflammation and fibrosis in aging liver. Issue 12 (11th November 2021) - Mohammed, Sabira; Thadathil, Nidheesh; Selvarani, Ramasamy; Nicklas, Evan H.; Wang, Dawei; Miller, Benjamin F.; Richardson, Arlan; Deepa, Sathyaseelan S.
Abstract: Inflammaging, characterized by an increase in low‐grade chronic inflammation with age, is a hallmark of aging and is strongly associated with various age‐related diseases, including chronic liver disease (CLD) and hepatocellular carcinoma (HCC). Because necroptosis is a cell death pathway that induces inflammation through the release of DAMPs, we tested the hypothesis that age‐associated increase in necroptosis contributes to chronic inflammation in aging liver. Phosphorylation of MLKL and MLKL oligomers, markers of necroptosis, as well as phosphorylation of RIPK3 and RIPK1 were significantly upregulated in the livers of old mice relative to young mice and this increase occurred in the later half of life (i.e., after 18 months of age). Markers of M1 macrophages, expression of pro‐inflammatory cytokines (TNFα, IL6 and IL1β), and markers of fibrosis were all significantly upregulated in the liver with age and the change in necroptosis paralleled the changes in inflammation and fibrosis. Hepatocytes and liver macrophages isolated from old mice showed elevated levels of necroptosis markers as well as increased expression of pro‐inflammatory cytokines relative to young mice. Short‐term treatment with the necroptosis inhibitor, necrostatin‐1s (Nec‐1s), reduced necroptosis, markers of M1 macrophages, fibrosis, and cell senescence as well as reducing the expression of pro‐inflammatory cytokines in the livers of old mice. Thus, our data show for the first time that liver aging is associated with increased necroptosis and necroptosis contributes to chronic inflammation in the liver, which in turn appears to contribute to liver fibrosis and possibly CLD. Abstract : Necroptosis increases with age in the liver and paralleled an increase in the expression of proinflammatory cytokines and markers of fibrosis. Hepatocytes and liver macrophages are the major cell types that undergo necroptosis in the livers of old mice. Short term treatment with the necroptosis inhibitor, necrostatin‐1s (Nec‐1s), reduced necroptosis, expression of proinflammatory cytokines and fibrosis in the livers of old mice.